Effects of glucose, ethanol and acetic acid on regulation of ADH2 gene from Lachancea fermentati - Yaacob, Norhayati; Mohamad Ali, Mohd Shukuri; Salleh, Abu Bakar; Abdul Rahman, Nor Aini (PeerJ, 2016)
Background. Not all yeast alcohol dehydrogenase 2 (ADH2) are repressed by glucose, as reported in Saccharomyces cerevisiae. Pichia stipitis ADH2 is regulated by oxygen instead of glucose, whereas Kluyveromyces marxianus ADH2 is regulated by neither glucose nor ethanol. For this reason, ADH2 regulation of yeasts may be species dependent, leading to a different type of expression and fermentation efficiency. Lachancea fermentati is a highly efficient ethanol producer, fast-growing cells and adapted to fermentation-related stresses such as ethanol and organic acid, but the metabolic information regarding the regulation of glucose and ethanol production is still lacking. Methods. Our investigation started with the stimulation of ADH2 activity from S. cerevisiae and L. fermentati by glucose and ethanol induction in a glucose-repressed medium. The study also embarked on the retrospective analysis of ADH2 genomic and protein level through direct sequencing and sites identification. Based on the sequence generated, we demonstrated ADH2 gene expression highlighting the conserved NAD(P)-binding domain in the context of glucose fermentation and ethanol production. Results. An increase of ADH2 activity was observed in starved L. fermentati (LfeADH2) and S. cerevisiae (SceADH2) in response to 2% (w/v) glucose induction. These suggest that in the presence of glucose, ADH2 activity was activated instead of being repressed. An induction of 0.5% (v/v) ethanol also increased LfeADH2 activity, promoting ethanol resistance, whereas accumulating acetic acid at a later stage of fermentation stimulated ADH2 activity and enhanced glucose consumption rates. The lack in upper stream activating sequence (UAS) and TATA elements hindered the possibility of Adr1 binding to LfeADH2. Transcription factors such as SP1 and RAP1 observed in LfeADH2 sequence have been implicated in the regulation of many genes including ADH2. In glucose fermentation, L. fermentati exhibited a bell-shaped ADH2 expression, showing the highest expression when glucose was depleted and ethanol-acetic acid was increased. Meanwhile, S. cerevisiae showed a constitutive ADH2 expression throughout the fermentation process. Discussion. ADH2 expression in L. fermentati may be subjected to changes in the presence of non-fermentative carbon source. The nucleotide sequence showed that ADH2 transcription could be influenced by other transcription genes of glycolysis oriented due to the lack of specific activation sites for Adr1. Our study suggests that if Adr1 is not capable of promoting LfeADH2 activation, the transcription can be controlled by Rap1 and Sp1 due to their inherent roles. Therefore in future, it is interesting to observe ADH2 gene being highly regulated by these potential transcription factors and functioned as a promoter for yeast under high volume of ethanol and organic acids.